Studi Kasus Serat Eceng Gondok Pada Produk Kerajinan Di Industri Kreatif Bengok Craft - Aisyah Aisyah; Felix Ari Dartono (Institut Seni Indonesia Surakarta, 2022)
Rawa Pening has many benefits as farming abd fishery resources. But now, the whole surface is covered by weeds like the water hyacinth. The water hyacinth utilized have been applied in the Rawa Pening area by using it to be a crafstmen product. To become a craft product of work, the water hyacinth must go through many processes. This study focused on analysis of the waterc hyacinth fiber in the creative industry Bengok Craft. Industrial materials produced by Bengok Craft have their own signature. This research ids descriptive qualitative research using method or way of thinking M.A.C.A.K from Guspara. The result of this study can be concluded several things: 1) the water hayicnth fiber can be served as materials hand made of many processes. The material of a product is closely related to the creation of works/products. The water hyacinth fiber is processed with various techniques/processed affect the characteristics/uniqueness of the Bengok Craft products. 2) the implementation of the water hyacinth fiber in the creative industry Bengok Craft in some products in the form of home decor, fashion, and merchandise products.